071 Causes of death in AQP4-IgG neuromyelitis optica spectrum disorder. Issue 6 (27th May 2022) - Gibbons, Emily; Everett, Rosie; Whittam, Daniel; Karthikeayan, Venkatraman; Messina, Silvia; Radu, Simona; Leite, Maria Isabel; Palace, Jacqueline; Huda, Saif; Jacob, Anu
Abstract : Objective: To evaluate causes of death in Aquaporin-4 antibody positive Neuromyelitis Optica Spectrum Disorder (AQP4-IgG NMOSD) patients treated in the National NMOSD service. Method: Retrospective review of Liverpool and Oxford patient databases (NMOSD national referral centres) between January 2010–2020. Results: AQP4-IgG NMOSD=414 patients attended the NMOSD Service and 34 died. Of these, 32/34(94%) were female with a median disease duration of 10 years (0.5–19.1). The median age at death was 67.1(45.1–88.3) years. Median EDSS score prior to death was 8(2–9.5). The median number of relapses from disease onset to death was 3(0–10), with 94% of patients experiencing at least 1 relapse. All but one patient was immunosuppressed (Azathioprine=15, Mycophenolate=3, Rituximab=7, Methotrexate=4, IVIg=1, Ciclosporin=1, Eculizumab=1, Prednisolone=1). Causes of death were available in 31/34 patients; infections=18, coronary artery disease=5, malignancy=4, bowel obstruction=1 and respiratory failure=2. Only one patient died from an acute brain stem relapse. Conclusion: Approximately 1 in 10 AQP4-NMOSD patients died over a 10-year period. The majority of patients had significant disability, suggesting possible association with NMOSD mortality. Infection was the leading cause of death, suggesting a possible relationship with immunosuppression. Striking a balance between disease suppression and mitigation of side effects poses a significant challenge in autoimmune neurological conditions. emily.gibbons@doctors.org.uk